Investigating the effectiveness and typology of teachers’ interactional feedback in supporting digital game-based language learning - Alghamdi, Abdulmajeed (Frontiers in Education, 2025)
This mixed-method experimental study investigates the effectiveness and typology of interactional feedback in supporting digital game-based language learning, focusing on two groups of primary language teachers. The experimental group employed interactional feedback within digital game-based language learning, while the comparison group used interactional feedback in traditional teaching methods. Results showed that the experimental group experienced statistically significant improvements in interactional feedback across three assessment points, whereas the comparison group showed no significant changes. The teachers in the experimental group employed a range of interactional feedback strategies, with notable improvements in clarification requests, recasts, and metalinguistic cues. Conversely, the comparison group primarily relied on repetition and direct correction, showing limited variation in their feedback approaches. Results also revealed that teachers in the experimental group significantly shifted their conceptions of interactional feedback, focusing not only on addressing interaction issues but also on recognizing the importance of uptake, output modification, and fostering student engagement through enriched screen time and enhanced teacher-student interactions. Further research should be encouraged and supported to develop digital games that prioritize teacher-student interaction, specifically by integrating interactional feedback as a standard feature. Collaborations between industry and researchers could play a crucial role in creating designs that effectively enhance interaction.